Arabidopsis Class I α-Mannosidases MNS4 and MNS5 Are Involved in Endoplasmic Reticulum–Associated Degradation of Misfolded Glycoproteins - Hüttner, Silvia (American Society of Plant Biologists, 2014)
To ensure that aberrantly folded proteins are cleared from the endoplasmic reticulum (ER), all eukaryotic cells possess a mechanism known as endoplasmic reticulum–associated degradation (ERAD). Many secretory proteins are N-glycosylated, and despite some recent progress, little is known about the mechanism that selects misfolded glycoproteins for degradation in plants. Here, we investigated the role of Arabidopsis thaliana class I α-mannosidases (MNS1 to MNS5) in glycan-dependent ERAD. Our genetic and biochemical data show that the two ER-resident proteins MNS4 and MNS5 are involved in the degradation of misfolded variants of the heavily glycosylated brassinosteroid receptor, BRASSINOSTEROID INSENSITIVE1, while MNS1 to MNS3 appear dispensable for this ERAD process. By contrast, N-glycan analysis of different mns mutant combinations revealed that MNS4 and MNS5 are not involved in regular N-glycan processing of properly folded secretory glycoproteins. Overexpression of MNS4 or MNS5 together with ER-retained glycoproteins indicates further that both enzymes can convert Glc(0-1)Man(8-9)GlcNAc(2) into N-glycans with a terminal α1,6-linked Man residue in the C-branch. Thus, MNS4 and MNS5 function in the formation of unique N-glycan structures that are specifically recognized by other components of the ERAD machinery, which ultimately results in the disposal of misfolded glycoproteins.